Quantitative analysis in femur of Wistar rats after chemotherapy treatment for breast cancer using synchrotron X‐ray microfluorescence and microtomography†. (22nd May 2015) - Pickler, A.; Alessio, R.; Mota, C. L.; Mantuano, A.; Nogueira, L. P.; Salata, C.; Almeida, A. P.; Sena, G.; Braz, D.; de Almeida, C. E. V.; Barroso, R. C.
<x xml:space="preserve">Abstract</x> In recent years, new techniques have been developed for the analysis of bone matrix. Two of the most common technologies that make use of X‐rays are X‐ray microfluorescence (μXRF) and X‐ray absorption microtomography (μCT). μXRF is a powerful analytical tool for the spectroscopic determination of almost all elements (Z > 13) present in a sample. μCT is a nondestructive technique, which can be used to create cross sections of complex objects. In this work, both techniques were applied to bones to evaluate possible structural and elemental modifications caused by chemotherapy procedure. Ten adult female Wistar rats, clinically healthy, divided randomly into two groups: treated group (called G1) received doses of docetaxel and cyclophosphamide drugs, while control group (called G0) was not treated. The elemental distribution of Ca and morphometric parameters, cortical porosity and bone volume–total tissue volume ratio in femur head, was investigated using μXRF and μCT, respectively, with the aim of helping to obtain a better understanding of the side effects caused by chemotherapy treatment for breast cancer. Calcium distribution maps were obtained by μXRF in the X‐ray fluorescence beamline at the Brazilian Synchrotron Light Laboratory. Morphometric parameters were calculated from three‐dimensional microtomographic images carried out at the Synchrotron Radiation on Medical Physics beamline at the Elettra Synchrotron Laboratory in Trieste, Italy. As a result of this study using μXRF, Ca levels show a significant decrease in treated bones in comparison with the control group. From μCT analysis, bone volume–total tissue volume ratio shows a tendency to decrease, while cortical porosity shows significant increase in bones from G1 group. Copyright © 2015 John Wiley & Sons, Ltd.